2015
DOI: 10.1038/onc.2015.476
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of tumor-suppressor MST1 in Hippo pathway induces its degradation through HBXIP-elevated HDAC6 in promotion of breast cancer growth

Abstract: Reduction or loss of tumor-suppressor mammalian STE20-like kinase 1 (MST1) in Hippo pathway contributes to the tumorigenesis. However, the mechanism leading to reduction of MST1 in cancers remains poorly understood. In this study, we explored the hypothesis that the oncoprotein hepatitis B X-interacting protein (HBXIP) is involved in the reduction of MST1 in breast cancer. Immunohistochemical analysis of tissue microarrays revealed that the expression of HBXIP was negatively associated with that of MST1 in 98 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 53 publications
3
60
0
1
Order By: Relevance
“…Our results suggest that the second core part of Hippo signaling, MST2 protein, is neither involved in ccRCC progression nor in YAP1 regulation. Although MST1/2 kinases have been acknowledged as tumor-suppressor proteins since loss of function of MST1/2 was observed in prostate (46) and breast cancer (47), and a decreased MST1 mRNA level was associated with node metastasis in colorectal cancer (48), however, in hepatocellular carcinoma HepG2 cells increased MST1/2 levels were reported (49). Decreased MST1 expression was associated with promoter methylation of this gene in soft tissue sarcomas (50).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Our results suggest that the second core part of Hippo signaling, MST2 protein, is neither involved in ccRCC progression nor in YAP1 regulation. Although MST1/2 kinases have been acknowledged as tumor-suppressor proteins since loss of function of MST1/2 was observed in prostate (46) and breast cancer (47), and a decreased MST1 mRNA level was associated with node metastasis in colorectal cancer (48), however, in hepatocellular carcinoma HepG2 cells increased MST1/2 levels were reported (49). Decreased MST1 expression was associated with promoter methylation of this gene in soft tissue sarcomas (50).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…HDAC6 has two features that distinguish it from all the other HDACs: it is exclusively cytoplasmic and it has two catalytic domains (Gregoretti et al 2004). Initially described to be a specific alpha-tubulin deacetylase, HDAC6 was later found to deacetylate other substrates, including tau, heat-shock protein 90, the actin binding protein cortactin, the tumor suppressor macrophage stimulating 1 and the beta-catenin transcription factor Li et al 2008Li et al , 2016Kekatpure et al 2009;Cook et al 2014). Both the neuroprotective and neurotoxic effects of HDAC6 have been associated with altered acetylation of target proteins, not a result of histone acetylation and ensuing effects on chromatin (Table 1).…”
Section: Hdac6mentioning
confidence: 99%
“…Studies have shown that highly expressed HBXIP leads to the promotion of breast cancer development. 28,29 Herein, we evaluated the relationship between ZEB1 and HBXIP in regard to breast cancer malignancy. The levels of ZEB1 and HBXIP in clinical breast cancer samples were examined.…”
Section: Hbxip-upregulated Zeb1 Enhances Breast Cancer Cell Proliferamentioning
confidence: 99%